2021
DOI: 10.1111/jog.14870
|View full text |Cite
|
Sign up to set email alerts
|

Long intergenic noncoding RNA 00473 promoting migration and invasion of trophoblastic cell line HTR‐8/SVneo via regulating miR‐424‐5p‐mediated wnt3a/β‐catenin signaling pathway

Abstract: Background: Preeclampsia (PE) is a serious obstetric complication. Recent studies point out that the functions of long intergenic noncoding RNA 00473 (linc00473), miR-424-5p, and Wnt/β-catenin signaling pathway were involved in the invasion and migration of extravillous trophoblast. Here, we investigated the role and mechanism of linc00473 in HTR-8/SVneo trophoblastic cell line and its role in PE. Method: The expression levels of linc00473 and miR-424-5p in placental tissues and the transfection efficiency of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…Among these targets, miR-424 regulates estrogen-related receptor γ to suppress trophoblast proliferation and invasion ( 50 ). Moreover, miR-424 targeted Wnt3a to influence Wnt/β-catenin signaling pathway and then affected the proliferation, apoptosis, migration and invasion of trophoblast cell line HTR-8/SVneo ( 51 ). In addition to Wnt/catenin signaling pathway, miR-424 also wields its function by regulating other pathways, such as PI3K/AKT signaling pathway in PE ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among these targets, miR-424 regulates estrogen-related receptor γ to suppress trophoblast proliferation and invasion ( 50 ). Moreover, miR-424 targeted Wnt3a to influence Wnt/β-catenin signaling pathway and then affected the proliferation, apoptosis, migration and invasion of trophoblast cell line HTR-8/SVneo ( 51 ). In addition to Wnt/catenin signaling pathway, miR-424 also wields its function by regulating other pathways, such as PI3K/AKT signaling pathway in PE ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…knockdown in trophoblast cell lines significantly inhibites cell proliferation and promotes apoptosis, whereas overexpression stimulates trophoblast proliferation. Further, linc00473 inhibited the expression of tissue factor pathway inhibitor 2 (TFPI2) through binding to lysinespecific demethylase 1 (LSD1) [177] mediates decidualization of human endometrial stromal cells in response to cAMP signaling [178] downregulation facilitates trophoblast cell migration and invasion via the miR-15a-5p/LITAF axis in pre-eclampsia, [179] Linc00473 mediates regulation of Wnt/β-catenin signaling pathway by miR-424-5p and affects invasion and migration of the trophoblastic cell line HTR-8/SVneo [180] PRNCR1 promotes the progression of PE by modulating the MAPK signaling pathway [181] CCAT1 is highly expressed in PE and can promote the progression of PE by inhibiting the expression of CDK4 [182] MEG3 is lower expressed in the placenta of patients with PE, and its regulation of trophoblast cell epithelial-mesenchymal transition via the TGF-β pathway inhibitor SMAD7 may be the molecular mechanism involved in the pathogenesis of PE [183] TUG1 is modulating proliferation in trophoblast cells via epigenetic suppression of RND3 [184] is modulating proliferation, apoptosis, invasion, and angiogenesis via targeting miR-29b in trophoblast cells [185] is regulating the migration and invasion of trophoblast-like cells through sponging miR-204-5p [186] lnc-DCs overexpression in dendritic cells mediates their maturation by phosphorylating STAT3 and induces the over-maturation of decidual dendritic cells in PE and leads to an increase in Th1 cells [187] RPAIN regulates the invasion and apoptosis of trophoblast cell lines via complement protein C1q [188] ATB down-regulated in PE placentas which was found to decrease migration, proliferation, and tube-formation of HTR-8/SVneo cells [189] Table 3. Cont.…”
Section: Lncrna Function Citationmentioning
confidence: 99%
“…[ 39 ] Previous study confirmed that the Wnt/β-catenin signaling pathway is of significant importance to the migration and invasion of tumors. [ 40 ] What’s more, Han’s study recommended the downregulation of lncRNA LINC00473 to attenuate the radioresistence of head and neck SCC cells through inhibiting Wnt/β-catenin signaling pathway. [ 40 ] A large body of evidence has demonstrated that LINC00473 might activate hepatocellular carcinoma progression by participating in signaling pathway of phosphatidylinositol-3-kinase/protein kinase B/the mammalian target of Rapamycin, which fortified cell proliferation, migration, invasion, and metastasis.…”
Section: Disscusionmentioning
confidence: 99%
“…[40] What's more, Han's study recommended the downregulation of lncRNA LINC00473 to attenuate the radioresistence of head and neck SCC cells through inhibiting Wnt/β-catenin signaling pathway. [40] A large body of evidence has demonstrated that LINC00473 might activate hepatocellular carcinoma progression by participating in signaling pathway of phosphatidylinositol-3-kinase/ protein kinase B/the mammalian target of Rapamycin, which fortified cell proliferation, migration, invasion, and metastasis. [41] It is known to all that chemoradiotherapy is beneficial for the patients with advanced cancers.…”
Section: Disscusionmentioning
confidence: 99%